Heaven and Hell : From magic carpets to drones. - Boghossian, Jean; De Coninck, François; Ghislain, Yves; Hennebert, Diane; Chamayou, Gregoire; Dosogne, Christophe (Bruxelles : Fondation Boghossian, 2015)
Al-Ani, Jananne ; Arrechea, Alexandre ; Bahir, Bilal ; Brechensbauer, Axel ; Cardenas, Solano ; Cherri, Ali ; Chishty, Mahwish ; Eleven Play ; Shahroudy Farmanfarmaian, Monir ; Framis, Alicia ; Garabedian, Mekhitar ; Golkar, Babak ; Grasso, Laurent ; Gicquel, Greygouar/Gregoire ; Guo-Qiang, Cai ; Harvey, Adam ; Iocose ; Ivanov, Pravdoliub ; Janssens, Edouard ; Josseau, Alain ; Jugnet + Clairet ; Kazemi, Babak ; Kennardphillipps ; Kintera, Kristof ; Leresteux, Julien ; Lüthi, Urs ; Malphettes, Pierre ; Matisse, Jackie ; Moshiri, Farhad ; Murayama, Macoto ; Muriuki, James & Syowia Kyambi, Miriam ; Panamarenko ; Pater, Ruben ; Plateus, Frederic ; Reuze, Sebastien ; Rousseau, Samuel ; Sarr, Moussa ; Schülke, Björn ; Sepehr, Jalal ; Tiravanija, Rirkrit ; Wagenknecht, Addie ; Wei, Li
Tentoonstelling 'Heaven and Hell. From magic carpets to drones.', Villa Empain, Bruxelles, 06.03.2015 - 06.09.2015.
Frans
Engels
boek